A comparison of the DNA binding and bending capacities and the oligomeric states of the immunity repressors of heteroimmune coliphages P2 and WΦ - Ahlgren-Berg, Alexandra (Oxford University Press, 2007)
Bacteriophages P2 and WΦ are heteroimmune members of the P2-like family of temperate Escherichia coli phages. Temperate phages can grow lytically or form lysogeny after infection. A transcriptional switch that contains two con-vergent promoters, Pe and Pc, and two repressors regulate what life mode to enter. The immunity repressor C is the first gene of the lysogenic operon, and it blocks the early Pe promoter. In this work, some characteristics of the C proteins of P2 and WΦ are compared. An in vivo genetic analysis shows that WΦ C, like P2 C, has a strong dimerization activity in the absence of its DNA target. Both C proteins recognize two directly repeated sequences, termed half-sites and a strong bending is induced in the respective DNA target upon binding. P2 C is unable to bind to one half-site as opposed to WΦ, but both half-sites are required for repression of WΦ Pe. A reduction from three to two helical turns between the centers of the half-sites in WΦ has no significant effect on the capacity to repress Pe. However, the protein–DNA complexes formed differ, as determined by electrophoretic mobility shift experiments. A difference in spontaneous phage production is observed in isogenic lysogens.